Proceedings of the 8th International Conference on Computer Supported Education 2016
DOI: 10.5220/0005810801540161
|View full text |Cite
|
Sign up to set email alerts
|

Learning Tracking Data Analysis - How Privacy Issues Affect Student Perception on e-Learning?

Abstract: Research works from the past ten years have demonstrated that technologies could in many ways enhance learning experience. Meanwhile, technologies can also create obstacles to the latter. For instance, using tracking approaches on the majority of e-learning platforms to monitor learners' activities raises many privacy questions. As for learners, knowing that their personal data are being used, even for educational purposes, they could radically change their perception on e-learning technologies. This paper pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…There was also no significant difference between genders in terms of students' awareness of their learning behaviours being monitored and recorded by their instructors. The researchers found that this was in line with previous studies about students' awareness of their privacy in the online learning environment (Doring, Hodge, & Heo, 2014;Lorenz, Sousa, & Tomberg, 2013;May, Fessakis, Dimitracopoulou, & George, 2012;May, Iksal & Usener, 2016;Yang & Wang, 2014). One possible interpretation is that, although students' ages were not known in this study, it may be assumed that most of them were from either the millennial generation or generation X, and were familiar with social media such as Facebook, Snapchat and/or Instagram, and therefore already knew about issues relating to users' data privacy (Gogus & Saygın, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…There was also no significant difference between genders in terms of students' awareness of their learning behaviours being monitored and recorded by their instructors. The researchers found that this was in line with previous studies about students' awareness of their privacy in the online learning environment (Doring, Hodge, & Heo, 2014;Lorenz, Sousa, & Tomberg, 2013;May, Fessakis, Dimitracopoulou, & George, 2012;May, Iksal & Usener, 2016;Yang & Wang, 2014). One possible interpretation is that, although students' ages were not known in this study, it may be assumed that most of them were from either the millennial generation or generation X, and were familiar with social media such as Facebook, Snapchat and/or Instagram, and therefore already knew about issues relating to users' data privacy (Gogus & Saygın, 2019).…”
Section: Discussionsupporting
confidence: 87%